International Broadcasting Convention, RAI Congress and Exhibition Centre, Amsterdam, The Netherlands, 16-20 September 1994 : [conference papers] - International Broadcasting Convention (1994 : Amsterdam, The Netherlands) (Stevenage, UK : IEE, 1994)
16